STRATEGI PENDIDIKAN AGAMA ISLAM DI LAPAS ANAK KUTOARJO ( STUDI KASUS REMAJA DI LAPAS ANAK KUTOARJO, JAWA TENGAH ) - Maisyanah, Maisyanah (El -Hekam, 2016)
The juvenile delinquency continues to increase due to internal and external factors of education. The internal factors were from the teachers as one of the main components in dealing directly with the students, but they do not have the right strategy to minimize the delinquency. External factors were from the community and the government as an educational evaluator. The method used in this research was descriptive qualitative. Data collection methods used were interview, observation, and documentation. The analysis used two kinds of triangulation and SWOT analysis. The results showed that the teachers in choosing a strategy is monotonous. It was happened, because unqualified teachers of PAI, limited facilities and infrastructure. Outside of learning, the learners have demonstrated good behavior in the prison. Other factors should be developed is prison’s environment that supports the potential development of learners.Keywords: Juvenile Delinquency, Teachers, Islamic Education, Prison, Anak Kutoarjo Central Java